Commonality in Liquidity: A Demand-Side Explanation - Koch, Andrew; Ruenzi, Stefan; Starks, Laura (Review of Financial Studies, 2016)
We hypothesize that a source of commonality in a stock's liquidity arises from the correlated liquidity demand of the stock's investors. Focusing on correlated trading of mutual funds, we find that stocks with high mutual fund ownership have comovements in liquidity about twice as large as those for stocks with low mutual fund ownership. Further analysis shows that the channels for these comovements derive from both common ownership across funds and funds' correlated liquidity shocks. We obtain inferences supporting causality from an exogenous flow shock for mutual funds in the aftermath of the 2003 mutual fund scandal.